FORMAT PEMILU SERENTAK PASCA PUTUSAN MK NO. 55/2019: Kajian dan Analisis Sosiologi Politik - Syarifuddin Jurdi (Jurnal Sosiologi Reflektif, 2020)
In the practice of the Indonesian presidential system, the presidential elections held after the legislative elections do not strengthen the presidential system, checks and balances mechanism  between the government and the People’s Representative Council have not run according to the mandate of the constitution yet. By using hermeneutic and verstehen approaches, as well as political sociology perspective, this paper considers that strengthen checks and balances mechanism between the government and People’s Representative Council is by carrying out regional and national simultaneous elections. The merging of legislative elections (People’s Representative Council and Regional representative Council) and presidential elections at national level also merging legislative and executive elections at  regional level have several functions:  first, the merging will result an effective and efficient governance in running the government; second, an easier and lighter electoral unification model, both for organizers in preparing stages of elections or for voters in channeling their voting rights; third, political issues that are programmed by candidate pairs and legislative candidates will be more focused and directed so that the public is clearer in determining their political choices. Dalam praktik sistem presidensial Indonesia, pemilu presiden yang diselenggarakan setelah pemilu legislatif tidak memperkuat sistem presidensial, mekanisme saling mengawasi (checks and balances) antara pemerintah dan DPR belum berjalan sesuai konstitusi. Dengan menggunakan pendekatan hermeneutik dan verstehen serta perspektif sosiologi politik dan kelembagaan, tulisan ini memandang bahwa memperkuat checks and balances antara pemerintah dan parlemen melalui penyelenggaraan pemilu serentak nasional dan lokal. Penggabungan pemilu legislatif (DPR dan DPD) dan pemilu presiden pada level nasional serta penggabungan pemilu legislatif (DPRD Provinsi dan DPRD kabupaten/kota) dan eksekutif (gubernur, bupati, walikota) pada level daerah menjadi pilihan; pertama, penyatuan tersebut akan menghasilkan pemerintahan yang efektif dan efisien dalam menjalankan kekuasaannya; kedua, model penyatuan level pemilu lebih mudah dan ringan, baik bagi penyelenggara dalam menyiapkan tahapan maupun bagi pemilih dalam menyalurkan hak pilihnya; ketiga, isu politik yang diprogramkan pasangan calon maupun calon legislatif akan lebih fokus dan terarah sehingga masyarakat lebih jelas dalam menentukan pilihan politiknya.